Dictionary of Privacy, Data Protection and Information Security - Elliot, Mark; Mandalari, Anna M; Mourby, Miranda; O’Hara, Kieron (Edward Elgar Publishing, 2024)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. The Dictionary of Privacy, Data Protection and Information Security explains the complex technical terms, legal concepts, privacy management techniques, conceptual matters and vocabulary that inform public debate about privacy.